TEKNIK SELF MANAGAMENT MENGATASI KESULITAN MENGATUR WAKTU BELAJAR SISWA MENENGAH ATAS MELALUI PENDEKATAN BEHAVIORAL - Wulan, Karima; Zainiyah, Zainiyah; Sa'adah, Nailis; Nadiyah, Hasanatun (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study will discuss self-management techniques for students struggling with time management at MA Mabdaul Falah Pamekasan through a behavioral approach. Difficulties in managing time include low responsibility for assignments, poor time management, and students being late to class. The purpose of this study is to help students manage their time and learn to manage it to improve their learning progress. The research method used is descriptive qualitative research. Data were collected through interviews and observations of MA Mabdaul Falah students. The results of this study indicate that self-management techniques for managing time can change student behavior. Students can manage their time and manage their behavior, leading to more positive outcomes.